Baseline psychophysiological and cortisol reactivity as a predictor of PTSD treatment outcome in virtual reality exposure therapy. (July 2016) - Norrholm, Seth Davin; Jovanovic, Tanja; Gerardi, Maryrose; Breazeale, Kathryn G.; Price, Matthew; Davis, Michael; Duncan, Erica; Ressler, Kerry J.; Bradley, Bekh; Rizzo, Albert; Tuerk, Peter W.; Rothbaum, Barbara O.
Abstract: Baseline cue-dependent physiological reactivity may serve as an objective measure of posttraumatic stress disorder (PTSD) symptoms. Additionally, prior animal model and psychological studies would suggest that subjects with greatest symptoms at baseline may have the greatest violation of expectancy to danger when undergoing exposure based psychotherapy; thus treatment approaches which enhanced the learning under these conditions would be optimal for those with maximal baseline cue-dependent reactivity. However methods to study this hypothesis objectively are lacking. Virtual reality (VR) methodologies have been successfully employed as an enhanced form of imaginal prolonged exposure therapy for the treatment of PTSD. Our goal was to examine the predictive nature of initial psychophysiological (e.g., startle, skin conductance, heart rate) and stress hormone responses (e.g., cortisol) during presentation of VR-based combat-related stimuli on PTSD treatment outcome. Combat veterans with PTSD underwent 6 weeks of VR exposure therapy combined with eitherd -cycloserine (DCS), alprazolam (ALP), or placebo (PBO). In the DCS group, startle response to VR scenes prior to initiation of treatment accounted for 76% of the variance in CAPS change scores, p < 0.001, in that higher responses predicted greater changes in symptom severity over time. Additionally, baseline cortisol reactivity was inversely associated with treatment response in the ALP group, p = 0.04. We propose that baseline cue-activated physiological measures will be sensitive to predicting patients' level of response to exposure therapy, in particular in the presence of enhancement (e.g., DCS). Highlights: Virtual reality (VR) enhances exposure therapy for posttraumatic stress disorder. Treatment was a 6-week VR exposure regimen withd -cycloserine, alprazolam, or placebo. In the DCS group, elevated startle before VR therapy predicted better outcome. Psychophysiological responses may serve as predictors of treatment outcome.